Participatory art within, against and beyond financialization: benign pessimism, tactical parasitics and the encrypted common. Issue 4 (4th July 2018) - Haiven, Max
ABSTRACT: This essay examines three critical artists who orchestrate participatory spectacles and experiences as a means of challenging neoliberal financialization, an overarching paradigm and process that is reshaping economics, politics, society and culture. Critical art, I argue, can offer us a particularly insightful vantage point on these transformations. This is not, as it is usually supposed, because art has some lofty transcendental perspective above society; rather, it is precisely because art is already so deeply integrated into finance and financialization. Not coincidentally, "participation" appears as a keyword for the restructuring of both art and finance today, which I argue is key to understanding the challenges, limits and potentials of even avowedly critical participatory art, with lessons for cultural production more broadly. In order to analyse and draw broader lessons from the three artworks in question, I identify each with a strategic paradigm: benign pessimism, tactical parasitism and the encrypted common. These strategies, I argue, emerge within, against and beyond financialization and can help complicate our approach to its complex cultural politics.